TINJAUAN HUKUM PELAKSANAAN HAK PERTUNJUKAN (PERFORMING RIGHT) PERUSAHAAN KARAOKE DALAM PEMBAYARAN ROYALTI LAGU MELALUI KUASA LEMBAGA MANAGEMENT KOLEKTIF: LEGAL REVIEW OF THE IMPLEMENTATION OF KARAOKE COMPANY'S PERFORMANCE RIGHTS IN PAYING SONG ROYALTY THROUGH THE POWER OF COLLECTIVE MANAGEMENT INSTITUTION - Moh. Fathur Rizki; Makkawaru, Zulkifli; Madiong, Baso (Faculty Of Law Bosowa University, 2021)
This study aims to determine the implementation of performance rights in terms of payment of copyright royalties to creators and copyright holders at karaoke companies in the city of Makassar, to know about the implementation of Copyright royalty management by the Collective Management Institute in Makassar City, and to find out the implementation of the sanctions imposed on karaoke companies that violate the obligation to pay royalties to creators.The research method used is juridical empirical. This research was conducted at the Karya Cipta Indonesia Office in the Makassar area, the Office of the Ministry of Law and Human Rights in South Sulawesi, the Inul Vizta karaoke company and local artists or songwriters as the copyright holders. The implementation of performance rights in the payment of royalties to creators and copyright holders in Makassar City has been well implemented even though the collection mechanism is carried out by LMKN, but at the time the payment is submitted to LMK in the regions. Although it is still found that there are small-scale user businesses that have not fully entered into cooperation contracts with LMK which are still foreign to him. The implementation of performance rights is supported by the existence of the latest regulations in the Copyright Law and awareness of supporting institutions such as the Regional Office of Law and Human Rights in general socialization. The management of royalties at LMK in Makassar City is only in the form of distribution of payments, while at the stage of collection to entrepreneurs who use songs and music, it is handled directly by LKMN. The imposition of sanctions in violation of royalty payments for businesses using songs and music cannot be said to have been fully implemented because the data on violations of performance rights has not been seen in synchronization of data between the regional LMK and the LMKN between the collection and distribution of royalties.